POU1F1 transcription factor promotes breast cancer metastasis via recruitment and polarization of macrophages. Issue 3 (27th August 2019) - Seoane, Samuel; Martinez‐Ordoñez, Anxo; Eiro, Noemi; Cabezas‐Sainz, Pablo; Garcia‐Caballero, Lucia; Gonzalez, Luis O; Macia, Manuel; Sanchez, Laura; Vizoso, Francisco; Perez‐Fernandez, Roman
Abstract: Cancer progression requires cells surrounding tumors be reeducated and activated to support tumor growth. Oncogenic signals from malignant cells directly influence stromal composition and activation, but the factors mediating this communication are still not well understood. We have previously shown that the transcription factor POU class 1 homeobox 1 (POU1F1), also known as Pit‐1, induces profound changes on neoplastic cell‐autonomous processes favoring metastasis in human breast cancer. Here we describe for the first time Pit‐1‐mediated paracrine actions on macrophages in the tumor microenvironment by using cell lines in vitro, zebrafish and mouse models in vivo, and samples from human breast cancer patients. Through the release of CXCL12, Pit‐1 in tumor cells was found to mediate the recruitment and polarization of macrophages into tumor‐associated macrophages (TAMs). In turn, TAMs collaborated with tumor cells to increase tumor growth, angiogenesis, extravasation and metastasis to lung. Our data reveal a new mechanism of cooperation between tumor cells and macrophages favoring metastasis and poor clinical outcome in human breast cancer, which suggests that Pit‐1 and CXCL12 should be further studied as potential prognostic and therapeutic indicators. © 2019 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.